Effect of binary blended pozzolanic materials on properties of self-compacting concrete. Issue 7 (19th May 2022) - Muhammad, A.; Usman, N.; Gambo, N.
Abstract: The mechanism of achieving self-compacting concrete (SCC) leads to either high shrinkage or it affects the mechanical properties of the concrete. Therefore, there is a need for blended pozzolanic materials for the production of SCC to improve its properties. The tests conducted on the fresh SCC were filling ability, passing ability, segregation resistance. While on the hardened SCC were density, compressive strength, tensile strength, water absorption, and ultrasonic pulse velocity test. At a fresh stage, the addition of the blend improved the flow and segregation resistance of the SCC produced. SCC produced with the addition of up to 20% of the blends at 7 days of curing had an 8% higher strength. At 150 days, all the SCC specimens have the same range of strength. The water absorption capacity of SCC with the addition of the blend up to 20% was found to be 12% less than that of the control specimens. Cement replaced with up to 20% blend of RHA and MK can be used to produce SCC with improved early (7 days) and later strength. It is recommended that when SCC is to be produced with a blend of RHA and MK, 20% is the optimum level of cement replacement.